2011
DOI: 10.1007/s11130-011-0232-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Soluble Ginseng Extract Induces Apoptosis and G0/G1 Cell Cycle Arrest in NCI-H460 Human Lung Cancer Cells

Abstract: This study was performed to elucidate the anticancer mechanism of a lipid-soluble ginseng extract (LSGE) by analyzing induction of apoptosis and arrest of cell cycle progression using the NCI-H460 human lung cancer cell line. Proliferation of NCI-H460 cells was potently inhibited by LSGE in a dose-dependent manner. The cell cycle arrest at the G0/G1 phase in NCI-H460 cells was induced by LSGE. The percentage of G0/G1 phase cells significantly increased, while that of S phase cells decreased after treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…8 For in vitro tests, LSGE was dissolved in dimethyl sulfoxide (DMSO) and further diluted with the culture media such that the final concentration of DMSO did not exceed 0.1%. 15 For in vivo tests, LSGE was dissolved in ethanol and further diluted in sterilized distilled water such that the final ethanol concentration was 4% before oral administration. 8,14 Proliferation assay B16F10 mouse melanoma cell line (American Type Culture Collection, Manassa, VA) was cultured in Dulbecco's modified Eagle's medium (DMEM) containing 10% fetal bovine serum (FBS) and 100 lg/mL of streptomycin sulfate.…”
Section: Preparation Of Lsgementioning
confidence: 99%
See 3 more Smart Citations
“…8 For in vitro tests, LSGE was dissolved in dimethyl sulfoxide (DMSO) and further diluted with the culture media such that the final concentration of DMSO did not exceed 0.1%. 15 For in vivo tests, LSGE was dissolved in ethanol and further diluted in sterilized distilled water such that the final ethanol concentration was 4% before oral administration. 8,14 Proliferation assay B16F10 mouse melanoma cell line (American Type Culture Collection, Manassa, VA) was cultured in Dulbecco's modified Eagle's medium (DMEM) containing 10% fetal bovine serum (FBS) and 100 lg/mL of streptomycin sulfate.…”
Section: Preparation Of Lsgementioning
confidence: 99%
“…Cell proliferation assays were performed using an XTT (sodium 3 0 -[1-(phenylaminocarbonyl)-3,4-tetrazolium]-bis (4-methoxy-6-nitro) benzene sulfonic acid hydrate) Cell Proliferation Kit II (Roche, Indianapolis, IN) as previously described. 15 B16F10 cells were plated at 1 · 10 4 cells/well in 96-well culture plates, incubated overnight, and treated with 0.1% DMSO (vehicle control), 0.3, 1.0, 3.0, or 10.0 lg/mL of LSGE for 24 h. Then, a XTT labeling reagent and electron-coupling reagent were added to each well according to the manufacturer's instructions. After the mixtures were incubated for 2 h at 37°C, the formazan dye was measured at 490 and 650 nm using a microplate reader (Molecular Devices, Sunnyvale, CA).…”
Section: Preparation Of Lsgementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to linoleic, palmitic, oleic and linolenic fatty acids and principal sesquiterpene components [4,5], polyacetylenes including panaxytriol, falcarinol and ginsenoyne A-K are present in ginseng as typical diyne lipid components [1,[6][7][8]. Recent studies reported that the nonpolar components of ginseng have antioxidant, antimicrobial, antitumor and anti-obesity activities [9][10][11][12]. A compound having pharmacological activity (such as falcarinol) could be found among them [13].…”
Section: Introductionmentioning
confidence: 99%